Keupayaan penyampaian jurulatih dan kesannya terhadap tahap kefahaman pelatih di Agensi AntiDadah Kebangsaan Negeri Johor - Rahmat, Fazrullah (2013)
This study aim to investigate trainers delivery ability and its impact on trainee understanding level in National Anti-Drug Agency Johore State during Course Support Help Group – 12 Steps held on 29 November 2012 to 30 November 2012. There are four objectives to be achieved in this study are: (i) identify the ability of trainers in delivering training programs from the perspective of trainees, (ii) identify trainee understanding level on programme content before and after training, (iii) identify relationship between trainers delivery ability with trainee understanding level before and after learning training programme and (iv) identify effect between trainers delivery ability with trainee understanding level on learning training programme before and after training. Questionnaire were distributed to 108 officers at National Anti-Drug Agency Johore State which follow Course Support Help Group – 12 Steps. In this study, SPSS version 16.0 used by researcher to analyze the results. The first and second objectives of the study as mentioned above have been achieved through descriptive analysis by looking at the mean and standard deviation scores. Meanwhile, for the third and fourth objective analysis based on inferensi methods to see Pearson’s correlation and regression. The results showed that the delivery ability of trainers and trainee level understanding during the Course Support Help Group – 12 Steps to be at a high level. Delivery ability of trainers are also connected in one way with the trainee level of understanding and have a medium relationship. The study also found that there is a significant effect between delivery ability of the trainers and trainee level of understanding during the Course Support Help Group – 12 Steps in National Anti-Drug Agency Johore State.